Rail power conditioner based on indirect AC/DC/AC modular multilevel converter using a three-phase V/V power transformer - Tanta, Mohamed (2017)
This paper presents a rail power conditioner (RPC) system based on an indirect AC/DC/AC modular multilevel converter (MMC) where a V/V power transformer is used to feed the main catenary line and the locomotives. The proposed control strategy for this system has been introduced to guarantee a good compensating performance of negative sequence currents (NSCs) and harmonics on the public grid side. This control strategy has also the ability to achieve balanced and equal voltage between the MMC’s submodules (SMs) capacitors. Simulation results for this RPC based on an indirect MMC are presented in this paper to show the main advantages of using this topology. The results show how the proposed system is able to compensate NSCs and harmonics on the public grid side when the V/V power transformer feeds two unequal load sections.